Investigation of monthly variations in the efficiencies of photovoltaics due to sunrise and sunset times - Armstrong O. Njok; Julie C. Ogbulezie; Manoj Kumar Panjwani; Raja Masood Larik (Institute of Advanced Engineering and Science, 2020)
The effect of time of day and month on the efficient conversion of solar energy to electrical energy using a polycrystalline (PV) module in calabar was studied. A KT-908 precision digital hygrometer and thermometer, and a M890C+ digital multimeter were used in the process. Results obtained shows that photovoltaic produce different levels of peak efficiencies at different times of the day for different months due to the difference in sunrise and sunset times for the months. The results also indicated that photovoltaics will be more efficient in months with low average relative humidity couple with low panel temperature. A peak efficiency of 77% at 12:30 in the month of April was observed before dropping to 73% at 12:00 in the month of May, indicating that there might be further drop in efficiency as we proceed further into the year. Results also show that photovoltaics are more efficient before noon in the month of May than in April while the reverse will be observed in the afternoon.